Recognition of the Aceh kingdom system: Wali Nanggroe in Indonesia Republic system - Ridwan, Muhammad; Fauzi, .; Saputra, Jumadil; Ibrahim, Yahaya; Muhammad, Zikri (Opción, 2019)
This article investigates one of the governance systems inherited from the archipelago kingdom in Southeast Asia, namely the Wali Nanggroe (Aceh Guardian), which is a system of government under the Kingdom of Aceh. Of the goal of this research is analysing three steps using interactive methods: 1) Data reduction, 2) Display, and 3) Conclusion. This study believes the changes of political culture can disrupt the stability. The results showed that Wali Nanggroe is still relevant as the local political institution in the modern and democratic systems